Methodologies of Achieving Energy-Plus Building through Deep Investigation in The Building Energy Performance: Case Study of Existing Multipurpose Building in Dubai, UAE - ABUFAZA’, BILAL ADNAN (2021)
The inevitable relation between population and energy demand is deriving the humanity for thinking about safe sources to cover their energy needs especially after the global warming raised during the last decades resulted from the reliance on depleting the fossil fuel. Numerous number of initiatives along with promising solutions have been observed for reduction energy consumption and find alternative clean energy. Energy-Plus Building as one of the latest trends in the sustainable transformation and based on shifting the building from energy consumer to producer with extra energy yield during specific period was investigated with exploring the potentials and obstacles of applying the same in UAE. A multipurpose building in UAE was the chosen case study where the best methodology applied through IES-VE software simulation, starting from enhancing building envelops materials mainly on the roof to reach the desired U-Value. Moving forward for exploring the best PV orientation, inclination and type which is south, 25° and monocrystalline respectively, the required PV panels that can cover the beak day demand proposed on the roof and parking area. The excessive produced energy and utility bills savings contributes in reducing the payback period for the transformation process to less than five years.